1996
DOI: 10.1111/j.1365-2648.1996.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ward design on the well‐being of post‐operative patients

Abstract: Changes in the design of hospital wards have usually been determined by architects and members of the nursing and medical professions; the views and preferences of patients have seldom been sought directly. The Hospital Anxiety and Depression scale and the Disturbance Due to Hospital Noise questionnaire were administered to 64 female patients on bay and Nightingale wards together with a questionnaire designed for this study. Perceptions of social and physical factors of ward design were examined, and their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…The literature suggests that ill patients wanted nurses to be closer. 12,13,42 Some patients in our study reported a high level of connection with staff, with staff perceived to be giving them full attention, listening and interested in the patient as a person, while others felt a sense of disconnection. A study of cancer patients in Denmark 68 found that refuge from fellow patients was hard to achieve in multibedded rooms and the fact that personal conversations might be overheard by fellow patients caused important information to be withheld from health-care professionals.…”
Section: Design Implicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…The literature suggests that ill patients wanted nurses to be closer. 12,13,42 Some patients in our study reported a high level of connection with staff, with staff perceived to be giving them full attention, listening and interested in the patient as a person, while others felt a sense of disconnection. A study of cancer patients in Denmark 68 found that refuge from fellow patients was hard to achieve in multibedded rooms and the fact that personal conversations might be overheard by fellow patients caused important information to be withheld from health-care professionals.…”
Section: Design Implicationsmentioning
confidence: 96%
“…29 In other studies, patients rated privacy and personal space as important but they also said that when ill they wanted nurses to be closer. 12,13,42 There is also evidence of more speech privacy and higher patient-reported satisfaction with doctor and nurse communication in single room patient accommodation. 11 A study of patient-physician communication in the Netherlands suggested that patients find it easier to raise questions with staff during ward rounds in single rooms than in multibedded rooms and feel that staff are more empathetic towards them.…”
Section: Box 1 Advantages and Disadvantages Of Single Rooms For Patiementioning
confidence: 96%
See 1 more Smart Citation
“…Such indicators included: job satisfaction (Tyson et al, 2002), staff turnover (Aiken et al, 2008;Applebaum et al, 2010), patient satisfaction (Douglas and Douglas, 2005;Stern et al, 2003) and patient privacy and dignity (Thrall, 2005). A well-designed, well laid-out, spacious and welldecorated accommodation environment is considered to significantly benefit both patient wellbeing and staff performance (Lorenz, 2007;Mroczek et al, 2005;Pattison and Robertson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…First, Pattison and Robertson (1996) compared a bay ward (bays of four or more beds parallel with the corridor and the external wall) with a Nightingale ward (long, single, open-plan room) where female patients were nursed after surgical procedures involving similar degrees of post-operative discomfort. Patients scored higher on disturbance due to noise on the Nightingale ward than on the bay ward, but no differences were found in sleep scores.…”
Section: Spatial Layoutmentioning
confidence: 99%